Early onset breast cancer in Ashkenazi women carriers of founder BRCA1/2 mutations: beyond 10 years of follow‐up. (10th October 2016) - Dagan, E.; Gershoni‐Baruch, R.; Kurolap, A.; Fried, G.
Abstract : This study uncovers disease characteristics by long‐term follow‐up in Ashkenazi early onset breast cancer (EOBC) patients, carriers of founder BRCA1/2 mutations compared to non‐carriers of such mutations. An archives‐retrospective design was conducted to study the pathological and clinical characteristics of 149 Ashkenazi Jewish EOBC patients (<42 years) who were referred consecutively to the oncogenetic clinic by the oncology centre at Rambam HealthCare Campus, as from 1995, with a mean follow‐up of 13.61 years. Of 149 patients, 33 (22.1%) and 15 (10.1%) carried the founder BRCA1 (185delAG; 5382insC) and BRCA2 (6174delT) mutations, respectively; and 101 (67.8%) were non‐carriers of these mutations. Contralateral breast‐cancer was predominant among BRCA1 / 2 carriers compared to non‐carriers (14, 58.3%; 6, 60%; 7, 8.1%; respectively, p  < .001). Ovarian cancer was diagnosed in two BRCA1 carriers and one non‐carrier. Oestrogen and/or progesterone receptor negative tumours were majorly detected in BRCA1 carriers ( n  = 16, 57.1%) compared to BRCA2 carriers ( n  = 4, 30.8%) and non‐carriers ( n  = 23, 25.3%) ( p  = .007). BRCA1 carriers and non‐carriers developed contralateral breast cancer at an earlier age than BRCA2 carriers. BRCA2 carriers portrayed similar tumour characteristics to non‐carriers. EOBC BRCA1/2 carriers are at risk to develop bilateral disease; however, they are similarly susceptible for local recurrence, distant metastases and mortality.